A política dos Arranjos Produtivos Locais (APLs) e seus condicionantes socioeconômicos em regiões periféricas como o Brasil - Rafaella Stradiotto Vignandi; Angelo Rondina Neto; Mateus Boldrine Abrita (Confins)
The objective of this paper is to analyze the evolution of public policies based on LPAs for Brazil in a recent period, considering some typical socioeconomic conditions of a country classified as peripherical. After the analysis it was not possible to clearly identify that the public policies of incentives to the LPAs in Brazil provided effective solutions to the places that received them. The contribution of the article was to verify that there is still inequality in the distribution of public policies throughout the Brazilian territory, lacking strategic actions and clear guidelines to help these peripheral regions to stimulate their local potentialities. Public policies proved to be relevant for the development, mainly local; however, it is still very concentrated in certain Brazilian regions.